2013
DOI: 10.1159/000353109
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of the Association between Adenovirus 36 Antibody Status and Weight Loss among Youth

Abstract: Objective: Although the human adenovirus 36 (Ad-36) is associated with obesity and relative hypolipidemia, its role in pediatric weight loss treatment response is uncertain. Therefore, the primary study objective was to determine whether Ad-36 antibody (AB) status was associated with response to a pediatric weight loss program. The secondary objective was to assess the association between Ad-36 AB status and baseline lipid values. Methods: Participants included 73 youth aged 10-17 years in a residential camp-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
23
0
2
Order By: Relevance
“…In one longitudinal study, positivity to Ad36 was associated with improved fasting insulin levels over time in normal‐weight participants, and with increased percent body fat in males with BMI higher than 25 kg m −2 . Diet‐induced weight loss was greater in adults, but lesser in children who had a previous exposure to Ad36 infection .…”
Section: Resultsmentioning
confidence: 99%
“…In one longitudinal study, positivity to Ad36 was associated with improved fasting insulin levels over time in normal‐weight participants, and with increased percent body fat in males with BMI higher than 25 kg m −2 . Diet‐induced weight loss was greater in adults, but lesser in children who had a previous exposure to Ad36 infection .…”
Section: Resultsmentioning
confidence: 99%
“…Association of adenovirus with human obesity was first revealed in 1997, where an avian adenovirus SMAM‐1 was reported to be linked to obesity in humans . Subsequently, Ad36 was reported to be associated with human obesity in several epidemiological studies from China, Czech Republic, India, Italy, Mexico, South Korea, Poland‐Sweden, Turkey, and United States . Most of the studies were observational which examined the presence of antibody against the Ad36 virus in human serum by serum neutralization assay or by an Enzyme‐Immuno Absorbant method.…”
Section: Resultsmentioning
confidence: 99%
“…Adv36 accelerates the differentiation of preadipocytes into adipocytes (Vangipuram et al 2004, Pasarica et al 2008 and stimulates fat accumulation in adipocytes, independently of insulin, dexamethasone and methyl-isobutyl-xanthine, substances acting as preadipocyte differentiation inducers (Rathod et al 2009). Adv36, but not Adv2, upregulates the expression of early, intermediate and late genes of the adipogenic cascade.…”
Section: The Mechanism Of Action Of Adenovirus 36mentioning
confidence: 99%
“…All were carried out in children and demonstrated that fat stores are preserved in response to a short-term weight management program. Weight loss during a 4-week summer weightloss camp in 73 young subjects aged 10-17 years was studied by Vander Wal et al (2013). At baseline, Adv36 seropositive and negative children did not differ in anthropometric and fitness measures, but Adv36 positive individuals showed lower levels of cholesterol and triglycerides.…”
Section: Adenovirus 36 and Weight Lossmentioning
confidence: 99%